A bibliometric study of the trend in articles related to epidemiology published in occupational health journals. Issue 7 (July 1996) - Takahashi, K; Hoshuyama, T; Ikegami, K; Itoh, T; Higashi, T; Okubo, T
Abstract : OBJECTIVES--To study the role assumed by epidemiology in occupational health literature and characterise its change over the years. METHODS--A bibliometric study was conducted with a MEDLINE search to evaluate 9024 articles published in eight representative occupational health journals for the period 1980-93. Articles related to epidemiology were found by descriptors indexed in the articles and their numbers and proportions among all published articles was tabulated for the study period. RESULTS--The proportion of source items indexed by epidemiology as a descriptor increased over threefold from 7.9% (42/534) in 1980 to over 25% after 1990. Epidemiology was indexed most frequently as a subheading associated with other descriptors-for example, occupational diseases-epidemiology. Cohort studies had the largest increase in the descriptors that indicated epidemiological type of studies during the period studied. CONCLUSION--Epidemiology is assuming increasing importance in occupational health literature. This was shown quantitatively and qualitatively by the use of descriptors in the MEDLINE database.